The use of virtual reality to boost the promotion of touristic destinations and the interpretation of heritage - Cunha, Carlos R. (2022)
Tourism and heritage are fundamental assets in many modern economies and certainly fundamental from a civilizational and generational point of view. Its promotion and interpretation are therefore important, and in these fields, technologies have played a fundamental and revolutionary role. In this scenario, Virtual Reality demonstrates an enormous potential in the promotion of destinations and in the creation of immersive experiences that allow a better interpretation of destinations and heritage, as well, as a greater attractiveness for the younger generations. This article, after reviewing concepts, proposes a conceptual model capable of contributing to a more agile and massified creation of Virtual Reality experiences. Finally, is presented an experimental prototype created for an olive oil museum, with the aim of facilitating the interpretation, by visitors, of its permanent exhibition objects.